A comparative study on indirect costs of suicide in Portugal: productivity loss as an additional way to approach healthcare prioritization. (3rd August 2021) - Neto, J; Carvalho, C; Almeida, P
Abstract: Background: Suicide and voluntary self-harm (SVSA) accounted for 0.95% of all deaths in Portugal in 2017. Economic evaluation includes indirect costs analysis, relating to Years of Life Lost (YLL) and premature death. This study aimed to estimate and compare the indirect costs from loss of productivity due to SVSA and 12 other causes of death in 2017. Methods: YLL were adapted to the working age (18–66 years-old) 'Years of Productivity Lost' (YPL) adjusting the groups 15–19 years-old and under, and disregarding the ages over 66 years-old. The causes of death were based on the European Shortlist. The loss of productivity from deaths was estimated from the YPL and the 'Apparent Productivity of Work', with an annual discount rate of 3%, translated into % of Gross Domestic Product (GDP) in 2017. The calculations were performed for the SVSA and for 12 causes of death selected from national Priority Health Programs. The INE and Pordata databases for the year 2017 were used. Calculations were performed using Microsoft Excel for Office 365 software version 2102. Results: The estimated costs from loss of productivity by SLAV deaths in 2017 represented approximately 0.16% of GDP. It is the third highest among the 13 causes of death analyzed, ranking behind malignant neoplasm of larynx/trachea/bronchi/lung and ischaemic heart disease. Conclusions: Prioritization of health resources may benefit by integrating lost productivity concepts with other indicators. Limitations include predictable increase of retirement age in the future and the oversimplified calculation of productivity costs. Future studies may include sensitivity assessments and other relevant variables.